PREPARATION OF LITHUANIAN POLICE OFFICERS - Janusauskas, Antanas; Aleksonis, Gediminas (European Scientific Journal, ESJ, 2013)
The article strives to disclose the higher police education at the Faculty of Public Security Mykolas Romeris University in Lithuania. The trends and developments in higher police education in Lithuania have generally confirmed the principal challenges identified in the Bologna Declaration – standardizes and integrates the Lithuanian education in the European Higher Education Area. Higher education can best assist police, in their great social work, by working with them to design, develop, deliver and evaluate full-fledged philosophies of police education. On this basis, all university programs have a strong focus on basic skills education. In management education in particular, this relies on the development, or at least the articulation, of normative and interrelated models of society and its police, and on the identification of empirically justifiable dispositions for practice and methods for teaching. This paper is part of a larger study into university education for police managers and presents the preliminary findings of the study.